The quasar M-BH-M-host relation through cosmic time - I. Data set and black hole masses - Decarli R; Falomo R; Treves A; Kotilainen JK; Labita M; Scarpa R (WILEY-BLACKWELL, 2025)
We study the M-BH-M-host relation as a function of cosmic time in a sample of 96 quasars from z = 3 to the present epoch. In this paper, we describe the sample, the data sources and the new spectroscopic observations. We then illustrate how we derive M-BH from single-epoch spectra, pointing out the uncertainties in the procedure. In a companion paper, we address the dependence of the ratio between the black hole mass and the host-galaxy luminosity and mass on cosmic time.